'What an awful body the UN have become!!'† Anglo-American–UN relations during the Congo crisis, February–December 1961. (2nd January 2016) - O'Malley, Alanna
Abstract : When Lord Salisbury passed the above remark in November 1961 it was at a moment of intense frustration for the British Foreign Office during the Congo crisis as the UN accelerated their efforts to restore territorial integrity to the Central African state by ending the secession of Katanga. The British viewed UN actions as a threat to their political and economic interests in the Congo and in Central Africa but crucially, also found that they were at loggerheads with the United States. This article examines Anglo-American relations at two key junctures in March and December 1961 when Britain successfully appealed to the United States to intervene in order to stall UN actions in the Congo. The cooperation between President John F. Kennedy and Prime Minister Harold Macmillan to constrain UN Congo policy reflects the centrality of the organisation in Anglo-American relations at the time and also highlights an understudied aspect of the relationship between the London and Washington. It will be shown that the crisis put a strain on the Anglo-American relations, leading to efforts by the British to play on the Cold War fears of the Americans by urging them to limit the actions of the UN. It is argued that the changing nature of the organisation helped to foster tensions in the Anglo-American relationship, exposing inherent differences of opinion about how American Cold War objectives should be balanced against the British agenda for decolonisation. The two incidents highlighted here reflect how the crisis became a challenge for Anglo-American relations and ultimately reveal the waning influence of the United States and the UK within the UN at the time.